Will Fishing Management Rules Diminish Angler’s Willingness To Fish - Barlian, Erland; Barlian, Nafi Putra (Indonesian Journal of Sport Management, 2024)
The aim of this paper is to oversee the moderation of management rules by the government to anglers satisfaction. We sruveys to 309 anglers from suburbans Jakarta area who actively doing recreational fishing as their leisure activity. We found that angler’s catch orientation that moderated by management rules both positive and negatifly influence the fishing satisfaction of doing their fishing activities. Despite the implementation of management rules the anglers embrace the government regulation for then no potential conflict between the recreational non commerciall and commerciall fishermen in the future. This management rules also being percieved as protector of the environment, preventing Illegal, Unreported, Unregulated fishing (IUU) and to ensure the sustainability of the economy that bourne from marine resources. Therefore we believe that this paper will give a clearer picture upon implementation of management rules to common pool resources sustainability as well as angler satisfaction in doing their fishing activities.